Cryptococcal meningitis in an immunocompetent swiftlet rancher – first reported case - Tan, Sin Nee; Lim, Christopher Thiam Seong (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Cryptococcal meningitis is a central nervous system infection cause by Cryptococcus neoformans. Although Cryptococcus is found in bird droppings, it has never been reported for those ranchers involved in the niche swiftlet ranching industry despite having close proximity with the bird droppings. We present here a case of a 41-year-old healthy swiftlet rancher who presents with a history of prolonged fever, headache and altered behaviour of a month duration. Cerebral spinal fluid analysis revealed the presence of Cryptococcus. He was treated with intravenous am-photericin B and flucytosine and discharged well with fluconazole consolidation therapy for 8 weeks, followed by maintenance therapy for 1 year. We believe this is the first reported case of Cryptococcal meningitis (CM) occurring in an immunocompetent swiftlet rancher. This case should highlight the needs to wear a proper personal protective equipment inside a swiftlet ranch due to the constant exposure to the potential cryptococcal-rich environment. A high index of suspicion, careful history taking and physical examination focusing on neurologic assessment is key to early diagnosis and timely management of CM.